Pattern Recognition and Image Analysis 4th Iberian Conference, IbPRIA 2009 Póvoa de Varzim, Portugal, June 10-12, 2009 Proceedings - Araújo, Hélder J.; Mendonça, Ana Maria; Pinho, Armando J.; Torres Barañano, María Inés (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2009)
This volume constitutes the refereed proceedings of the 4th Iberian Conference on Pattern Recognition and Image Analysis, IbPRIA 2009, held in Póvoa de Varzim, Portugal in June 2009. The 33 revised full papers and 29 revised poster papers presented together with 3 invited talks were carefully reviewed and selected from 106 submissions. The papers are organized in topical sections on computer vision, image analysis and processing, as well as pattern recognition.